MEDIA PEMBELAJARAN BOLA VOLI BERBASIS WEB (WORD ELECTRIC BROWSER) UNTUK SISWA SEKOLAH MENENGAH ATAS - Hakim, Luqman; Supriatna, Eka; Hidasari, Fitriana Puspa (Universitas Tanjungpura, 2024)
The problem of this research is the lack of use of interactive learning media in the learning process of physical education, especially volleyball. The purpose of the research is to create interesting, innovative, and easy-to-understand learning media, and to keep up with technological advances, especially high school volleyball material. This type of research uses the Research and Development (RD) ADDIE approach with the stages of analysis, planning, development, implementation, and evaluation. The research subjects were students and teachers of SMA N 3 Pontianak, with random sampling technique. The results of the study from the WEB page show that this learning media is interesting, innovative, and easy to understand. The media were validated and tested by experts, from media experts it showed 97.5% and from material experts it showed 87.5%, so that both were categorized as very valid, as well as conducting a feasibility test for students and teachers, showing the learning media studied were categorized as very high with 82.75 % and categorized as high with 77.97%. It can be concluded that the WEB-Based Learning Media product is